Variability and correlations of economically valuable traits in cowpea from the VIR collection in the environments of Astrakhan provincer - M. V. Gurkina (Труды по прикладной ботанике, генетике и селекции)
Background. The problem of a deficit in vegetable protein and the need to diversify agricultural produce require involvement of new and little-known crops, such as cowpea, in the production. Cowpea (Vigna unguiculata (L.) Walp.) is a high-protein leguminous crop; its breeding and production have been intensified in Russia only in recent years. The study of the VIR collection, carried out at the Institute’s branch in Astrakhan, makes it possible to disclose the crop’s breeding potential. Objective: Studying the range of variability and tracing the relationships of economically valuable traits in vegetable (green pod) cowpea under the conditions of Astrakhan Province.Materials and methods. In 2008‑2010, a study was implemented at an experiment plot of the Astrakhan branch of VIR. Thirty- three accessions of green pod cowpea from the VIR collection were studied to analyze the variability of 12 phenotypic traits. Positive and negative correlations were identified between the following characters: interphase periods (flowering, industrial ripeness and seed maturation), shape of the shrub, lengths of the stem and to the first pod, length and weight of the pod, number of seeds per pod, presence of a parchment layer and fiber in pod valves, pod yield per plant, number of pods and peduncles, seed weight per plant, and weight of 1000 seeds.Results and conclusion. Medium variability was observed for such characters as the interphase periods ‘shoots–industrial ripeness’ and ‘shoots– seed maturation’, number of seeds per pod, and weight of 1000 seeds: the coefficient of variation (CV) was 15‑18%. High variation was registered for the length and weight of the pod (CV = 26‑32%), shrub shape, stem length, and length of the stem up to the first pod (CV = 35‑37%). The widest ranges of variability were demonstrated in the quantitative yield characters of cowpea accessions: number of pods per plant (CV = 33‑49%), number of flower stalks (CV = 38‑51%), and seed weight per plant (CV = 38‑44%), which means that cowpea yield is quite susceptible to weather conditions. During the three years of studying, the lowest levels of variability in economically valuable traits were characteristic of the accessions of the early-ripening group: k‑668 and k‑873 (China); mid- ripening group: k‑971 (India); and late-ripening group: k‑141 (China). Cowpea pod productivity depended to the greatest degree from mean values of the number of pods per plant (r = 0,73) and the number of peduncles (r = 0,71). The identified correlations in the productivity components make it possible to optimize the selection of accessions promising as source materials for the development of new high-yielding cultivars.